Efektivitas Tipe Student Teams Achievement Devisions Terhadap Pemahaman Konsep dan Kemampuan Berpikir Tingkat Tinggi Dalam Pembelajaran Sistem Persamaan Linier Tiga Variabel Kelas X SMK Swasta Parulian 1 Medan T. A. 2025/2026 - sihotang, maria; Tambunan, Hardi; Hutauruk, Agusmanto J.B (Universitas PGRI Semarang, 2026)
This study aims to determine the effectiveness of the Student Teams Achievement Divisions (STAD) method on conceptual understanding and higher-order thinking skills in the teaching of systems of linear equations with three variables for 10th-grade students at Parulian 1 Private Vocational High School, Medan, Academic Year 2025/2026. The study population consists of all 10th-grade students, and the sample comprises 60 10th-grade students. The sampling technique used was Purposive Random Sampling. The instruments used were tests, questionnaires, and observations. The research results, as seen from the indicators of learning effectiveness, were met: the learning structure was in the “good” category, teacher communication was in the “good” category, student response was in the “good” category, student activity was in the “good” category, and learning achievement was in the “achieved” category. The research results indicate that the Student Teams Achievement Divisions (STAD) learning method is effective in enhancing conceptual understanding and higher-order thinking skills.